Biomechanical characterization of spider webs. (March 2017) - Das, Rakesh; Kumar, Amit; Patel, Anurag; Vijay, Sahil; Saurabh, Shashank; Kumar, Navin
Abstract: In light of recent focus on the behaviour of the natural structures for revolutionary technological growth, spider web seems to have seized considerable attention of product designer due to its amazing behaviour. In present work, mechanism behind the structural integrity of the spider web along with the materialistic analysis of its constituent silk threads has been extensively investigated. The nanoindentation tool both in static and dynamic mode has been utilized for complete analysis of the mechanical behaviour of the spiral and radial threads separately. Both the average elastic modulus and hardness of the radial silk thread is higher than the spiral silk thread which reveals the radial silk thread is the major structural component of the web. The sustainability of spider webs under storm, windy conditions and during the impact of pray has been investigated under dynamic conditions. The radial silk thread exhibits elastic like response and the spiral silk thread exhibits viscous like response in a wide frequency range (1–200 Hz). The damping characteristic of the radial and spiral silk threads, an important parameter to investigate the energy dissipation properties of the materials has also been investigated in windy conditions.